MENGEMBANGKAN KEPEMIMPINAN TRANSFORMASIONAL DI UPT SD: STRATEGI DAN TANTANGAN - Herlina, Besse; Arafah, Muhammad; Rohanah, Rohanah; Irmawanti, Andi; Masauleng, Masauleng; Rahmawati, Rahmawati; Pawe, Nisba (Pascasarjana Universitas Pendidikan Ganesha, 2025)
The implementation of transformational leadership in elementary schools continues to face various challenges. This study aims to analyse the strategies and challenges of transformational leadership in elementary school UPTDs through a qualitative case study approach. The research subjects were purposively selected principals and teachers, and data were collected through semi-structured interviews, participant observation, and document analysis. The analysis used thematic analysis by Broun & Clarke, with data reduction, thematic categorisation, and triangulation to enhance the validity of the findings. The results indicate that the main strategies implemented are teacher empowerment, developing a collaborative culture, and improving the quality of learning. Challenges faced include resistance to change, limited resources, and a lack of policy support. Schools with principals who implement this leadership model have a more harmonious work environment, increased teacher motivation, and better student learning outcomes. This study makes an important contribution to enriching the contextual understanding of transformational leadership practices in elementary schools and supporting the development of more relevant and sustainable policies and principal training.